2021
DOI: 10.1002/cam4.3664
|View full text |Cite
|
Sign up to set email alerts
|

Acute patient‐reported outcomes in B‐cell malignancies treated with axicabtagene ciloleucel

Abstract: Chimeric antigen receptor T‐cell therapy with axicabtagene ciloleucel (axi‐cel) has considerably improved survival in adults with relapsed/refractory large B‐cell lymphoma. This study reports patient‐reported outcomes (PROs) such as quality of life (QOL) and toxicity in the first 90 days after treatment. Hematologic cancer patients treated with axi‐cel ( N = 103, mean age = 61, 39% female) completed SF‐36 or PROMIS‐29 QOL questionnaires prior to treatment and 90 days after. PRO‐Common Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Patient-reported toxicity monitoring (measured with PRO-CTCAE) revealed peaks of symptoms such as cough, decreased appetite, dry mouth, fatigue, hair loss, hand-foot syndrome, headache, nausea, problems with concentration, problems with memory at 14 days after CAR T-cell infusion followed by decline over time. 48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-reported toxicity monitoring (measured with PRO-CTCAE) revealed peaks of symptoms such as cough, decreased appetite, dry mouth, fatigue, hair loss, hand-foot syndrome, headache, nausea, problems with concentration, problems with memory at 14 days after CAR T-cell infusion followed by decline over time. 48…”
Section: Resultsmentioning
confidence: 99%
“…Of these, we retrieved a total of 14 eligible studies reporting PRO results. 14,15,[45][46][47][48][49][50][51][52][53][54][55][56] Details of the search strategy and selection process of the articles included in this review were documented according to the PRISMA guidelines 57 and are reported in Figure 1.…”
Section: Data Extraction and Evaluationmentioning
confidence: 99%
“…[ 19 ] Similarly, 96% of patients with hematological malignancies treated with axi-cel reported fatigue with 84% reporting moderate to severe fatigue. [ 20 ] In a study comparing patient-reported quality of life and symptom burden after CAR T-cell therapy and other forms of cellular therapy, 44% of patients in the CAR T-cell group reported fatigue after treatment. [ 21 ] Furthermore, the conditioning chemotherapy that precedes CAR T-cell therapy may cause side effects such as pancytopenia, weakness, nausea, vomiting, poor appetite, and in severe cases neuropathy in the hands and feet, affecting physical function.…”
Section: Rehabilitation Interventions For Functional Declinementioning
confidence: 99%
“…1013 Most patients report long-term neuropsychiatric consequences, including depression, anxiety and cognitive impairment. 11,12,14 Perspectives from patients who fail to respond or progress rapidly following treatment are lacking. 6…”
Section: Introductionmentioning
confidence: 99%